2022
DOI: 10.1021/acsami.2c08301
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning-Based Predictions of Polymer and Postconsumer Recycled Polymer Properties: A Comprehensive Review

Abstract: There has been a tremendous increase in demand for virgin and postconsumer recycled (PCR) polymers due to their wide range of chemical and physical characteristics. Despite the numerous potential benefits of using a data-driven approach to polymer design, major hurdles exist in the development of polymer informatics due to the complicated hierarchical polymer structures. In this review, a brief introduction on virgin polymer structure, PCR polymers, compatibilization of polymers to be recycled, and their chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 156 publications
0
9
0
Order By: Relevance
“…In the past, attempts to solely rely on language models for polymer property prediction tasks were hindered by the scarcity and unattainability of high-quality labeled polymer datasets, 37 while the availability of high-quality open-source polymer datasets is steadily increasing. [38][39][40][41] More encouragingly, extensive work has shown that data augmentationbased approaches are effective in addressing the scarcity of polymer data, 15,42,43 and harnessing the intelligence of general language models proves benecial for comprehending scientic language via language models. [44][45][46][47] To the best of our knowledge, a completely end-to-end language-based approach for directly predicting the properties of polymers from natural and chemical languages, rather than being used as intermediates to connect molecular structures to downstream models, is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, attempts to solely rely on language models for polymer property prediction tasks were hindered by the scarcity and unattainability of high-quality labeled polymer datasets, 37 while the availability of high-quality open-source polymer datasets is steadily increasing. [38][39][40][41] More encouragingly, extensive work has shown that data augmentationbased approaches are effective in addressing the scarcity of polymer data, 15,42,43 and harnessing the intelligence of general language models proves benecial for comprehending scientic language via language models. [44][45][46][47] To the best of our knowledge, a completely end-to-end language-based approach for directly predicting the properties of polymers from natural and chemical languages, rather than being used as intermediates to connect molecular structures to downstream models, is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Another critical research direction is the application of ML in biopolymer recycling and waste reduction. ,, As the world grapples with plastic pollution, biopolymers offer a sustainable alternative. ML can be leveraged to improve recycling processes, optimize waste management systems, and develop new biodegradable materials.…”
Section: Future Workmentioning
confidence: 99%
“…[ 146 ] One of these describes the use of ML to predict the properties of recycled polymers, providing emphasis on fingerprinting, algorithms, open‐source databases, representations, and polymer design. [ 147 ] However, there are only a very few literature reports focusing on the optimization of polymer processing parameters related to, for example, melt processing, extrusion, or injection molding.…”
Section: Processing and Fabricationmentioning
confidence: 99%